ANALISIS KANDUNGAN ANTISEPTIK GETAH TUMBUHAN PATIKAN KEBO (Euphorbia hirta) SEBAGAI DASAR PEMBUATAN BROSUR PENANGANAN LUKA RINGAN PADA MASYARAKAT - Mahendra Widiarto; Muhammad Abdurrahman Janiarta; Putri Komala Intan; Titi Laily Hajiriah (Bioscientist : Jurnal Ilmiah Biologi, 2018)
Patikan Kebo (Euphorbia hirta) leaves are often used as traditional medicine and have been proven to be natural antiseptics. We use this society as a basis for analyzing its antiseptic content clinically through laboratory testing. The test results will then be presented in the form of a brochure. The brochure that will be distributed before going through the 4D model development stage. The method used in this study is the maceration method to proceed to the phytochemical test. The results of this study found the presence of iodine in the sap and alkaloid content and tanin through phytochemical tests through screening tests. The results of this study are then presented in the form of a brochure with a validation test from 2 experts obtaining an average score of 3.2 in the good category. Based on the results of the analysis it can be concluded that it is true that Patikan Kebo (Euphorbia hirta) contains antiseptic compounds that can heal wounds so that it can be informed to the public through a well-validated health brochure for distribution to the public.